PENGARUH DISIPLIN KERJA, KOMPENSASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI NEGERI SIPIL (PNS) DI BKPSMD KABUPATEN KERINCI - Setiawan, Suhendra; Elfiswandi, Elfiswandi; Yulasmi, Yulasmi (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 2 (2025): JISAMAR (March-May 2025), 2025)
This study, entitled "The Influence of Work Discipline, Compensation, and Work Culture on Employee Performance through Motivation as an Intervening Variable among Civil Servants at the BKPSDMD of Kerinci Regency," focuses on all Civil Servants (PNS) at the BKPSDMD of Kerinci Regency. The type of research used is descriptive quantitative research, with data collected through the distribution of questionnaires. The analytical method applied is multiple linear regression analysis using the SmartPLS version 3.0 software. The sampling technique employed is a saturated sample, involving the analysis of 70 respondents. Based on the results of the analysis, it can be concluded that work discipline has a positive and significant effect on work motivation, compensation has an insignificant effect on work motivation, and work culture has an insignificant effect on work motivation. Furthermore, work discipline has a positive and significant effect on employee performance, compensation has an insignificant effect on employee performance, and work culture has an insignificant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Work discipline also has a positive and significant effect on employee performance through work motivation, while compensation and work culture have insignificant effects on employee performance through work motivation.